Validity and reliability of catapult vector S7 GNSS units in distance measurement - Ocak, M. F.; Sentürk, D.; Akyildiz, Z. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Purpose This study aimed to evaluate the validity and reliability of the Catapult Vector S7 GPS device in measuring total distance in a simulated team sport environment, with the specific goal of providing practical guidance for its application in sports science and practice.